Exposome-based public health interventions for infectious diseases in urban settings - Andrianou, Xanthi; Pronk, Anjoeka; Galea, Karen S.; Stierum, Rob; Loh, Miranda M.; Riccardo, Flavia; Pezzotti, Patrizio; Makris, Konstantinos C. (My University, 2021)
The COVID-19 pandemic placed public health measures against infectious diseases at the core of global health challenges, especially in cities where more than half of the global population lives. SARS-CoV-2 is an exposure agent recently added to the network of exposures that comprise the human exposome, i.e. the totality of all environmental exposures throughout one's lifetime. At the same time, the application of measures to tackle SARS-CoV-2 transmission leads to changes in the exposome components and in characteristics of urban environments that define the urban exposome, a complementary concept to the human exposome, which focuses on monitoring urban health. This work highlights the use of a comprehensive systems-based approach of the exposome for better capturing the population-wide and individual-level variability in SARS-CoV-2 spread and its associated urban and individual exposures towards improved guidance and response. Population characteristics, the built environment and spatiotemporal features of city infrastructure, as well as individual characteristics/parameters, socioeconomic status, occupation and biological susceptibility need to be simultaneously considered when deploying non-pharmacological public health measures. Integrating individual and population characteristics, as well as urban-specific parameters is the prerequisite in urban exposome studies. Applications of the exposome approach in cities/towns could facilitate assessment of health disparities and better identification of vulnerable populations, as framed by multiple environmental, urban design and planning co-exposures. Exposome-based applications in epidemics control and response include the implementation of exposomic tools that have been quite mature in non-communicable disease research, ranging from biomonitoring and surveillance to sensors and modeling. Therefore, the exposome can be a novel tool in risk assessment and management during epidemics and other major public health events. This is a unique opportunity for the research community to exploit the exposome concept and its tools in upgrading and further developing site-specific public health measures in cities.
Keywords: COVID-19; Exposome; Interventions; Systems-based approach